Coexisting Germline CHEK2 and Somatic BRAF(V600E) Mutations in Papillary Thyroid Cancer and Their Association with Clinicopathological Features and Disease Course - Gąsior-Perczak, Danuta (Cancers (Basel), 2019)
BRAF(V600E) is the most common somatic mutation in papillary thyroid carcinoma (PTC) and the majority of evidence indicates that it is associated with an aggressive clinical course. Germline mutations of the CHEK2 gene impair the DNA damage repair process and increase the risk of PTC. Coexistence of both mutations is expected to be associated with poorer clinical course. We evaluated the prevalence of concomitant CHEK2 and BRAF(V600E) mutations and their associations with clinicopathological features, treatment response, and disease course in PTC patients. The study included 427 unselected PTC patients (377 women and 50 men) from one center. Relationships among clinicopathological features, mutation status, treatment response, and disease outcomes were assessed. Mean follow-up was 10 years. CHEK2 mutations were detected in 15.2% and BRAF(V600E) mutations in 64.2% patients. Neither mutation was present in 31.4% cases and both BRAF(V600E) and CHEK2 mutations coexisted in 10.8% patients. No significant differences in clinicopathological features, initial risk, treatment response, or disease outcome were detected among these patient groups. CHEK2 mutations were significantly associated with older age, while BRAF(V600E) was significantly associated with older age and extrathyroidal extension. The coexistence of both mutations was not associated with more aggressive clinicopathological features of PTC, poorer treatment response, or disease outcome.